Soft magnetic powder, dust core, magnetic element, and electronic apparatus

The soft magnetic powder, with a specific composition and oxide particle size, addresses the magnetic and insulating property issues in existing iron-based soft magnetic alloy powders, resulting in improved magnetic permeability and voltage resistance.

JP2025047238APending Publication Date: 2025-04-03SEIKO EPSON CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023155618
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-21
Publication Date
2025-04-03

AI Technical Summary

Technical Problem

The iron-based soft magnetic alloy powder described in Patent Document 1 faces issues where the addition of Al and Ca, intended to improve powder shape and reduce oxygen content, deteriorates magnetic properties and can lead to decreased insulating properties and withstand voltage if the oxygen content is too low.

Method used

The soft magnetic powder comprises metal particles and oxide particles on their surface, with a composition mainly consisting of Fe, Si (2.5% to 7.5% by mass), Cr (1.0% to 10.0% by mass), S (0.0020% to 0.0070% by mass), and impurities, where the average particle size of the oxide particles is between 0.2 μm and 2.0 μm, optimizing insulation and magnetic properties.

Benefits of technology

This configuration enables the production of a powder compact with excellent magnetic properties, high insulating properties between particles, and improved oxidation resistance, thereby enhancing the magnetic permeability and voltage resistance of the magnetic element.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025047238000001_ABST
    Figure 2025047238000001_ABST
Patent Text Reader

Abstract

To provide soft magnetic powder with which a green compact having good magnetic properties can be manufactured and in which particles are highly insulated from each other, a dust core and a magnetic element that include the soft magnetic powder, have good magnetic properties, and have a high withstanding voltage, and an electronic apparatus that comprises the magnetic element.SOLUTION: Soft magnetic powder has metal particles, and oxide particles present on the surface of each of the metal particles. The entire composition includes Fe as a main component, Si contained in an amount of 2.5 mass% or more and 7.5 mass% or less, Cr contained in an amount of 1.0 mass% or more and 10.0 mass% or less, S contained in an amount of 0.0020 mass% or more and 0.0070 mass% or less, and impurities. The average particle diameter of the oxide particles is 0.2 μm or more and 2.0 μm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a soft magnetic powder, a dust core, a magnetic element, and an electronic device. [Background technology]

[0002] Patent Document 1 discloses a crystalline iron-based soft magnetic alloy powder containing 0.5-10% by weight of Si, 0-7% by weight of Cr, 0.01-1.2% by weight of Al, and 0.001-0.01% by weight of Ca, with the remainder being Fe and unavoidable impurities. Such iron-based soft magnetic alloy powder has high fluidity, so that high packing can be achieved during molding. Therefore, high magnetic permeability can be achieved in a magnetic element having a dust core. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2020-111826 A Summary of the Invention [Problem to be solved by the invention]

[0004] In the iron-based soft magnetic alloy powder described in Patent Document 1, Al is added for the purpose of improving the shape of the powder and reducing the amount of oxygen in the powder. Ca is added for the purpose of reducing the amount of oxygen in the powder. However, these elements cause the magnetic properties of the powder to deteriorate. In addition, if the amount of oxygen is too low, the insulation between particles is reduced, which causes the withstand voltage of the magnetic element to decrease. [Means for solving the problem]

[0005] The soft magnetic powder according to the application example of the present invention is Metal particles; Oxide particles present on the surfaces of the metal particles; having The overall composition is: The main component is Fe, Si having a content of 2.5% by mass or more and 7.5% by mass or less; Cr with a content of 1.0 mass% or more and 10.0 mass% or less; S with a content of 0.0020% by mass or more and 0.0070% by mass or less; Impurities, It is composed of The oxide particles have an average particle size of 0.2 μm or more and 2.0 μm or less.

[0006] The powder magnetic core according to the application example of the present invention is The soft magnetic powder according to the application example of the present invention is included.

[0007] The magnetic element according to the application example of the present invention includes: The present invention is provided with a powder magnetic core according to an application example of the present invention.

[0008] The electronic device according to the application example of the present invention includes: The magnetic element according to the application example of the present invention is provided. [Brief description of the drawings]

[0009] [Figure 1] FIG. 2 is a schematic diagram showing the configuration of a soft magnetic powder according to an embodiment. [Diagram 2] FIG. 2 is a plan view illustrating a schematic diagram of a toroidal type coil component. [Diagram 3] FIG. 2 is a see-through perspective view that typically illustrates a closed magnetic circuit type coil component. [Figure 4] FIG. 1 is a perspective view showing a mobile personal computer, which is an electronic device including a magnetic element according to an embodiment. [Diagram 5] FIG. 1 is a plan view showing a smartphone, which is an electronic device including a magnetic element according to an embodiment. [Figure 6] FIG. 1 is a perspective view showing a digital still camera, which is an electronic device including a magnetic element according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The soft magnetic powder, the dust core, the magnetic element, and the electronic device of the present invention will be described in detail below with reference to preferred embodiments shown in the accompanying drawings.

[0011] 1. Soft magnetic powder FIG. 1 is a schematic diagram showing the configuration of a soft magnetic powder 1 according to an embodiment.

[0012] The soft magnetic powder 1 shown in Fig. 1 is an aggregate of a plurality of soft magnetic particles 5. The soft magnetic particle 5 has a metal particle 2 and one or more oxide particles 3 present on the surface thereof.

[0013] The metal particles 2 are made of an alloy having soft magnetic properties. The oxide particles 3 contain an oxide of an element contained in the metal particles 2. The average particle size of the oxide particles 3 is 0.2 μm or more and 2.0 μm or less.

[0014] The overall composition of the soft magnetic powder 1 is composed of Fe (iron) as the main component, Si (silicon) with a content of 2.5 mass% or more and 7.5 mass% or less, Cr (chromium) with a content of 1.0 mass% or more and 10.0 mass% or less, S with a content of 0.0020 mass% or more and 0.0070 mass% or less, and impurities.

[0015] With such soft magnetic powder 1, the oxide particles 3 ensure insulation between the metal particles 2, and a green compact with excellent voltage resistance can be produced. In addition, because the average particle size of the oxide particles 3 is optimized, even in the presence of the oxide particles 3, the soft magnetic powder 1 has excellent packing properties during compaction, and allows the production of a green compact with good magnetic properties.

[0016] The soft magnetic powder 1 may be used alone or in combination with particles other than the above-mentioned soft magnetic particles 5. Examples of the other particles include particles that do not contain oxide particles 3 (particles composed only of metal particles 2).

[0017] The soft magnetic powder 1 can be used for any purpose, but for example, the particles are bound together via a binder and used to produce various types of green compacts such as dust cores and electromagnetic wave absorbing materials.

[0018] 1.1. Composition Soft magnetic powder 1 is composed mainly of Fe (iron), with Si (silicon) content of 2.5 mass% or more and 7.5 mass% or less, Cr (chromium) content of 1.0 mass% or more and 10.0 mass% or less, S content of 0.0020 mass% or more and 0.0070 mass% or less, and impurities.

[0019] The main component refers to the element that has the highest content in terms of atomic ratio. Fe is the main component of Soft Magnetic Powder 1 and has a significant effect on the basic magnetic properties of Soft Magnetic Powder 1.

[0020] The Fe content is not particularly limited, but is preferably 80 mass % or more, and more preferably 90 mass % or more.

[0021] The Si content is set to 2.5% by mass or more and 7.5% by mass or less, preferably 2.7% by mass or more and 5.0% by mass or less, and more preferably 3.0% by mass or more and 4.5% by mass or less. If the Si content is within the above range, a green compact with higher magnetic permeability can be obtained. If the Si content is below the lower limit, magnetic properties such as magnetic permeability and DC bias characteristics are reduced. On the other hand, if the Si content exceeds the upper limit, the material becomes hard, and the density of the green compact is reduced.

[0022] The Cr content is 1.0% by mass or more and 10.0% by mass or less, preferably 1.0% by mass or more and 6.0% by mass or less, and more preferably 1.0% by mass or more and 5.0% by mass or less. If the Cr content is within the above range, the oxidation resistance of the soft magnetic powder 1 can be improved while maintaining the magnetic properties. This allows the oxide occupancy rate during compaction to be particularly low, and a soft magnetic powder 1 that can produce a compact with good magnetic properties can be obtained. If the Cr content is below the lower limit, the oxidation resistance of the soft magnetic powder 1 decreases. On the other hand, if the Cr content exceeds the upper limit, the magnetic properties such as magnetic permeability and DC superposition characteristics decrease.

[0023] The content of S is set to 0.0020% by mass or more and 0.0070% by mass or less, preferably 0.0030% by mass or more and 0.0060% by mass or less, and more preferably 0.0040% by mass or more and 0.0050% by mass or less. The content of S affects the oxygen content and particle shape of the soft magnetic powder 1. Specifically, the oxygen content of the soft magnetic powder 1 tends to be proportional to the content of S. In addition, the particle shape changes depending on the content of S. If the content of S is within the above range, the oxygen content of the soft magnetic powder 1 can be adjusted to an optimal range, and the particle shape can be easily made closer to a spherical shape. Note that, if the content of S is below the lower limit, the oxygen content of the soft magnetic powder 1 becomes too low. As a result, the insulation between the particles of the soft magnetic powder 1 decreases, and the voltage resistance of the green compact obtained by green compacting the soft magnetic powder 1 decreases. In addition, the particle shape of the soft magnetic powder 1 is easily irregular, and the density of the green compact decreases. As a result, the magnetic properties of the green compact, such as magnetic permeability, are degraded. On the other hand, when the S content exceeds the upper limit, the oxygen content of the soft magnetic powder 1 becomes too high. As a result, the oxide occupancy rate in the green compact obtained by compacting the soft magnetic powder 1 becomes high, and the magnetic properties, such as magnetic permeability, are degraded.

[0024] The mass ratio of the S content to the Cr content is defined as S / Cr. The mass ratio S / Cr is preferably 0.0004 or more and 0.0040 or less, more preferably 0.0006 or more and 0.0035 or less, and even more preferably 0.0010 or more and 0.0030 or less. If the mass ratio S / Cr is within the above range, the balance between the Cr content and the S content can be optimized. This allows both improvement of the packing property due to the particle shape and improvement of the magnetic properties due to the optimization of the composition. In addition, improvement of the oxidation resistance due to Cr can be enjoyed. As a result, a green compact having particularly good magnetic properties and excellent insulation between particles can be obtained.

[0025] If the mass ratio S / Cr is below the lower limit, the oxidation resistance of the soft magnetic powder 1 is improved, but the anisotropy of the particle shape increases, which may reduce the packing ability of the soft magnetic powder 1. On the other hand, if the mass ratio S / Cr is above the upper limit, the soft magnetic powder 1 is made spherical, but the oxidation resistance decreases, and the occupancy rate of the metal in the green compact may decrease.

[0026] In addition to the above elements, the soft magnetic powder 1 may contain other elements as impurities. The term "impurities" refers to elements other than the above elements that are inevitably mixed in.

[0027] The impurity concentration is preferably 0.10 mass% or less for each element, and more preferably 0.05 mass% or less. Furthermore, it is even more preferable that the concentration is lower than that of S in terms of atomic ratio. The total concentration of the impurities is preferably 1.00 mass% or less. Note that, within these ranges, the inclusion of other elements is permissible since it does not affect the effects of the soft magnetic powder 1.

[0028] Moreover, the soft magnetic powder 1 according to the embodiment contains oxygen as an impurity. Oxygen is mixed in the raw materials or during the manufacturing process. The oxygen content of the soft magnetic powder 1 is preferably 3000 ppm or less by mass, more preferably 2000 ppm or less, and even more preferably 1500 ppm or less. This suppresses the deterioration of the particle shape due to the mixing of oxygen, and thus a soft magnetic powder 1 having high packing property during compaction can be obtained. In addition, the decrease in the metal occupancy rate in the compact can be suppressed. On the other hand, the lower limit of the oxygen content is preferably 300 ppm or more, more preferably 500 ppm or more, from the viewpoint of ensuring the insulation between particles. This allows the insulation between particles to be sufficiently ensured, and a compact with suppressed eddy current loss can be obtained.

[0029] This oxygen exists as an oxide formed by the oxidation of any of the elements contained in the metal particles 2. At least a part of this oxide exists on the surface of the metal particles 2 as oxide particles 3. Therefore, the metal particles 2 are composed of, for example, the above composition excluding the oxide.

[0030] The above composition is specified by the following analytical method. Examples of analytical methods include iron and steel-atomic absorption spectrometry specified in JIS G 1257:2000, iron and steel-inductively coupled plasma atomic emission spectrometry specified in JIS G 1258:2007, iron and steel-spark discharge atomic emission spectrometry specified in JIS G 1253:2002, iron and steel-fluorescent X-ray analysis specified in JIS G 1256:1997, and gravimetry, titration, and absorptiometry specified in JIS G 1211 to G 1237.

[0031] Specific examples include a solid-state optical emission spectrometer manufactured by SPECTRO, in particular a spark discharge optical emission spectrometer, model: SPECTROLAB, type: LAVMB08A, and an ICP device, CIROS120 type manufactured by Rigaku Corporation.

[0032] In particular, for the identification of C (carbon) and S (sulfur), the oxygen flow combustion (high-frequency induction heating furnace combustion)-infrared absorption method specified in JIS G 1211: 2011 is also used. Specifically, the LECO carbon-sulfur analyzer, CS-200, can be mentioned.

[0033] Furthermore, in particular for the specification of N (nitrogen) and O (oxygen), the method for determining nitrogen in iron and steel specified in JIS G 1228:1997 and the general method for determining oxygen in metallic materials specified in JIS Z 2613:2006 are also used. Specific examples include LECO oxygen / nitrogen analyzers, TC-300 / EF-300, and LECO oxygen / nitrogen / hydrogen analyzer, ONH836.

[0034] 1.2.Oxide particles The oxide particles 3 contain oxides of the elements that constitute the metal particles 2. Therefore, examples of the constituent materials of the oxide particles 3 include iron oxide, silicon oxide, chromium oxide, and sulfur oxide. These oxides may contain oxides with different oxidation numbers. For example, the iron oxide may be composed of at least one of FeO, Fe2O3, and Fe3O4. The silicon oxide is composed of at least one of SiO and SiO2.

[0035] Of these, the oxide particles 3 preferably contain silicon oxide, and more preferably have silicon oxide as the main component. This makes it possible to obtain a soft magnetic powder 1 with particularly good insulation between particles. Incidentally, having silicon oxide as the main component means that, when elemental analysis is performed on the oxide particles 3 by energy dispersive X-ray analysis (EDX), the concentration of either oxygen or silicon is the highest, and the concentration of the other is the second highest.

[0036] The average particle size of the oxide particles 3 is 0.2 μm or more and 2.0 μm or less, preferably 0.3 μm or more and 1.5 μm or less, and more preferably 0.4 μm or more and 1.0 μm or less. By having the average particle size of the oxide particles 3 within the above range, it is possible to minimize the influence of the oxide particles 3 on the packing property during compaction of the soft magnetic powder 1 while ensuring the insulation between the particles of the soft magnetic powder 1. This makes it possible to obtain a soft magnetic powder 1 that has excellent packing property during compaction and can produce a compact having good magnetic properties.

[0037] If the average particle size of the oxide particles 3 is below the lower limit, the insulation between the particles of the soft magnetic powder 1 cannot be sufficiently ensured, the withstand voltage of the green compact decreases, and the eddy current flowing between the particles cannot be sufficiently suppressed. On the other hand, if the average particle size of the oxide particles 3 exceeds the upper limit, the filling property of the soft magnetic powder 1 during compaction decreases, and the magnetic properties of the green compact decrease.

[0038] The average particle size of the oxide particles 3 is measured as follows. First, an image (secondary electron image) of the soft magnetic particles 5 is taken with a scanning electron microscope (SEM). Next, the obtained image is loaded into image processing software. For example, image analysis type particle size distribution measurement software "Mac-View" manufactured by Mountech Co., Ltd. is used as the image processing software. The imaging magnification is adjusted so that one soft magnetic particle 5 is entirely captured in one image, and other soft magnetic particles 5 are only partially captured.

[0039] Next, in the particle image of the soft magnetic particle 5 in its entirety, the oxide particles 3 present on the surface of the metal particle 2 are identified based on the difference in shape and contrast. Then, the circular equivalent diameter of the oxide particles 3 is calculated using software. When multiple oxide particles 3 are present on one metal particle 2, the circular equivalent diameter is calculated for each oxide particle 3. However, when the circular equivalent diameter is 0.05 μm or less, it is not used as the calculated value.

[0040] Next, the circle-equivalent diameters of the oxide particles 3 are determined in the same manner as above for a total of 10 or more randomly selected particles. Then, the average value of the circle-equivalent diameters thus determined is calculated. The obtained average value is the average particle size of the oxide particles 3.

[0041] Furthermore, the number of oxide particles 3 present in one metal particle 2 is not particularly limited, but is preferably 20 or less, more preferably 2 to 15, and even more preferably 3 to 10. If the number of oxide particles 3 is within the above range, the oxide particles 3 are less likely to affect the packing of the green compact, while still enjoying the effect of ensuring insulation due to the oxide particles 3. As a result, a soft magnetic powder 1 that can be used to produce a high-density green compact can be obtained.

[0042] If the number of oxide particles 3 is below the lower limit, the insulation between the soft magnetic particles 5 may not be sufficiently ensured depending on the average particle size of the oxide particles 3. On the other hand, if the number of oxide particles 3 is above the upper limit, the density of the green compact may not be sufficiently increased depending on the average particle size of the oxide particles 3.

[0043] 1.3.Powder characteristics The average particle size of the soft magnetic powder 1 is preferably 1.0 μm or more and 20.0 μm or less, more preferably 3.0 μm or more and 15.0 μm or less, and further preferably 4.0 μm or more and 9.0 μm or less, thereby obtaining a soft magnetic powder 1 that has high packing properties during compaction and can suppress eddy current loss in the compact.

[0044] If the average particle size of the soft magnetic powder 1 is below the lower limit, the soft magnetic powder 1 is likely to aggregate, which may reduce the packing property and the density of the green compact. On the other hand, if the average particle size of the soft magnetic powder 1 is above the upper limit, the eddy current loss of the green compact may increase.

[0045] The average particle size refers to a particle size D50 at which the cumulative frequency is 50% from the small diameter side in a cumulative particle size distribution on a volume basis of the soft magnetic powder 1 obtained using a laser diffraction particle size distribution measuring device.

[0046] Moreover, the average particle size of the oxide particles 3 described above is preferably 1.5% to 25.0% of the average particle size of the soft magnetic powder 1, more preferably 2.0% to 20.0%, and even more preferably 3.0% to 15.0%. This optimizes the particle size ratio of the oxide particles 3 in the soft magnetic powder 1, and can improve both the insulation between the particles of the soft magnetic powder 1 and the packing property of the soft magnetic powder 1 during compaction. As a result, a soft magnetic powder 1 is obtained that can be used to produce a compact having high voltage resistance, low iron loss, and good magnetic properties.

[0047] If the ratio (particle size ratio) of the average particle size of the oxide particles 3 to the average particle size of the soft magnetic powder 1 is below the lower limit, the average particle size of the oxide particles 3 becomes relatively small, and there is a risk that the insulation between the particles of the soft magnetic powder 1 cannot be sufficiently ensured. On the other hand, if the particle size ratio exceeds the upper limit, the average particle size of the oxide particles 3 becomes relatively large, and the oxide particles 3 are more likely to affect the soft magnetic powder 1 when it is compressed, and there is a risk that the filling property decreases.

[0048] The average circularity of the soft magnetic powder 1 is preferably 0.80 or more and 0.95 or less, more preferably 0.82 or more and 0.92 or less, and even more preferably 0.85 or more and 0.90 or less. This makes it possible to obtain a soft magnetic powder 1 with particularly good packing properties when compacted. In addition, when an insulating film is formed on the particle surface of the soft magnetic powder 1, the film can be formed uniformly and without unevenness. This makes it possible to manufacture a compact with excellent insulation between particles. In addition, since a small amount of binder is required to bind the particles, the magnetic properties of the compact can be improved.

[0049] If the average circularity is below the lower limit, the filling property of the soft magnetic powder 1 during compaction may decrease. Also, the uniformity of the thickness of the insulating coating may decrease. On the other hand, if the average circularity is above the upper limit, the manufacturing difficulty of the soft magnetic powder 1 may increase.

[0050] The average circularity of the soft magnetic powder 1 (soft magnetic particles 5) is measured as follows. First, an image (secondary electron image) of the soft magnetic particles 5 is taken with a scanning electron microscope (SEM). Next, the obtained image is loaded into image processing software. For example, image analysis type particle size distribution measurement software "Mac-View" manufactured by Mountech Co., Ltd. is used as the image processing software. The imaging magnification is adjusted so that 50 to 100 particles are captured in one image. Then, multiple images are acquired so that a total of 300 or more particle images are obtained.

[0051] Next, using software, the circularity of 300 or more particle images is calculated and the average value is obtained. The obtained average value is the average circularity of the soft magnetic powder 1. Note that, when the circularity is e, the area of ​​the particle image is S, and the perimeter of the particle image is L, the circularity e can be obtained by the following formula. e=4πS / L 2

[0052] 1.4.Density of green compact The soft magnetic powder 1 according to the embodiment has a density of 5.40 g / cm when compacted. 3 More than 6.00g / cm3 It is preferable that the density is 5.45 g / cm or less. 3 More than 5.80g / cm 3 More preferably, it is 5.50 g / cm or less. 3 More than 5.70g / cm 3 It is more preferable that the soft magnetic powder 1 is equal to or less than 1.0 mm. Such soft magnetic powder 1 can realize a green compact having sufficiently high magnetic permeability while ensuring insulation between particles.

[0053] If the density is below the lower limit, the magnetic permeability of the green compact may decrease, whereas if the density is above the upper limit, the density of the green compact may vary significantly, resulting in large individual differences in magnetic permeability.

[0054] The density of the green compact is measured as follows. First, 2 mass% of epoxy resin (binder) and methyl ethyl ketone (solvent) are added to the soft magnetic powder 1 and mixed to obtain a mixed material. Next, the obtained mixed material is thoroughly stirred and dried by heating at a temperature of 150°C for 30 minutes. Next, the obtained dried body is sieved through a sieve with an opening of 600 μm and pulverized to obtain a granulated powder. Next, the obtained granulated powder is molded under the following molding conditions to obtain a molded body.

[0055] Molding method: Press molding Shape of molded body: Ring-shaped - Dimensions of molded body: outer diameter φ14mm, inner diameter φ8mm, thickness 3mm Molding pressure: 294MPa

[0056] Next, the binder in the compact is cured by heating, thereby obtaining a green compact. Next, the mass and volume of the obtained green compact are measured, and the density of the green compact is calculated based on the measurement results.

[0057] 1.5.Magnetic permeability The soft magnetic powder according to the embodiment preferably has a magnetic permeability of 24 or more at a measurement frequency of 1 MHz when compacted, and more preferably has a magnetic permeability of 26 or more. Such a soft magnetic powder can realize a compact having a sufficiently high magnetic permeability.

[0058] The magnetic permeability of the green compact is the real part μ' of the complex magnetic permeability, and is measured using a BH analyzer at a measurement frequency of 1 MHz. The number of turns of the winding around the green compact is 7, and the wire diameter of the winding is 0.5 mm. When manufacturing the green compact, an epoxy resin is used as a binder at a ratio of 2 mass% of the soft magnetic powder. The size of the green compact is an outer diameter of φ14 mm, an inner diameter of φ8 mm, and a thickness of 3 mm, and the molding pressure is 294 MPa.

[0059] 2. Manufacturing method of soft magnetic powder Next, an example of a method for producing the above-mentioned soft magnetic powder 1 will be described.

[0060] The soft magnetic powder 1 may be a powder produced by any method. Examples of the production method include various atomization methods such as water atomization, gas atomization, and rotary water flow atomization, as well as pulverization. Of these, the soft magnetic powder 1 is preferably a powder produced by the atomization method. The soft magnetic powder 1 described above can be produced efficiently by the atomization method.

[0061] The atomization method is a method for producing metal powder by colliding molten metal with a liquid or gas jetted at high speed to atomize and cool the metal. In the atomization method, the molten metal is atomized, and then spherical during the process of solidification, so that particles closer to perfect spheres can be produced.

[0062] The water atomization method uses a liquid such as water as a coolant, which is sprayed in an inverted cone shape so that it converges to one point, and molten metal is made to flow down toward this convergence point and collide with it, in order to produce metal powder from molten metal.

[0063] The rotary water jet atomization method is a method for producing metal powder by supplying a cooling liquid along the inner surface of a cooling cylinder and rotating it along the inner surface while spraying a liquid or gas jet onto molten metal and incorporating the scattered molten metal into the cooling liquid.

[0064] The gas atomization method uses gas as a cooling medium, sprays it in an inverted cone shape that converges to one point, and causes molten metal to flow down toward this convergence point and collide with it to produce metal powder from molten metal.

[0065] In these atomization methods, parameters such as the average particle size of the soft magnetic powder 1, the average circularity of the soft magnetic powder 1, the oxygen content, the average particle size of the oxide particles 3, and the number of the oxide particles 3 can be adjusted depending on the conditions.

[0066] The casting temperature of the melting temperature is preferably set to Tm+200°C or higher, more preferably Tm+220°C or higher and Tm+350°C or lower, and even more preferably Tm+250°C or higher and Tm+300°C or lower, relative to the melting point Tm [°C] of the constituent material of the soft magnetic powder 1. This allows the time during which the powder exists as a molten metal when it is refined by various atomization methods and solidifies to be optimized. This allows the average circularity of the soft magnetic powder 1, the average particle size of the oxide particles 3, the number of the oxide particles 3, and the like to be adjusted within the aforementioned ranges.

[0067] In addition, when the casting temperature is lowered, the time that the metal can exist as molten metal is shortened, and the average circularity is reduced. When the molten metal solidifies, oxides are precipitated to generate oxide particles 3, and when the casting temperature is lowered, the average particle size and number of the oxide particles 3 tend to become smaller. On the other hand, when the casting temperature is raised, the opposite tendency is observed.

[0068] In the atomization method, molten metal is made to flow down from a narrow opening, and the resulting molten metal stream is collided with a fluid jet. The outer diameter of the molten metal stream is not particularly limited, but is preferably 2.5 mm or less, more preferably 0.3 mm to 2.0 mm, and even more preferably 0.5 mm to 1.5 mm. This makes it easier to uniformly hit the molten metal with the fluid jet, making it easier to uniformly scatter droplets of a suitable size. As a result, the average particle size of the soft magnetic powder 1 can be adjusted within the above-mentioned range. In addition, since the cooling rate can be optimized, the average circularity of the soft magnetic powder 1, the oxygen content, the average particle size of the oxide particles 3, the number of the oxide particles 3, etc. can be adjusted within the above-mentioned range.

[0069] When the outer diameter of the molten metal stream is reduced, the average particle size of the soft magnetic powder 1 tends to decrease and the average circularity tends to decrease. Also, the oxygen content tends to increase slightly, and the average particle size and number of the oxide particles 3 tend to increase slightly. On the other hand, when the outer diameter of the molten metal stream is increased, the opposite tendency occurs.

[0070] Furthermore, the produced soft magnetic powder 1 may be classified as necessary. Examples of classification methods include dry classification such as sieving classification, inertial classification, and centrifugal classification, and wet classification such as sedimentation classification.

[0071] 3. Powder cores and magnetic components Next, the powder magnetic core and the magnetic element according to the embodiment will be described.

[0072] The magnetic element according to the embodiment can be applied to various magnetic elements having a magnetic core, such as a choke coil, an inductor, a noise filter, a reactor, a transformer, a motor, an actuator, an electromagnetic valve, a generator, etc. Furthermore, the powder magnetic core according to the embodiment can be applied to the magnetic cores included in these magnetic elements.

[0073] Two types of coil components will be described below as representative examples of the magnetic element. 3.1.Toroidal type First, a toroidal type coil component, which is an example of a magnetic element according to the embodiment, will be described.

[0074] FIG. 2 is a plan view that illustrates a schematic diagram of a toroidal-type coil component 10. As shown in FIG. 2 has a ring-shaped powder magnetic core 11 and a conductive wire 12 wound around this powder magnetic core 11. Such a coil component 10 is generally called a toroidal coil.

[0075] The powder magnetic core 11 is obtained by mixing the soft magnetic powder 1 according to the embodiment with a binder, supplying the mixture to a molding die, and pressing and molding it. Thus, the powder magnetic core 11 is a compact containing the soft magnetic powder 1 according to the embodiment. Such a powder magnetic core 11 has high magnetic properties, high voltage resistance, and low iron loss. Therefore, when the coil component 10 is mounted in an electronic device or the like, the electronic device or the like can be made more compact and have higher performance.

[0076] Examples of materials constituting the binder used in producing the powder magnetic core 11 include organic materials such as silicone resins, epoxy resins, phenol resins, polyamide resins, polyimide resins, and polyphenylene sulfide resins, and inorganic materials such as phosphates such as magnesium phosphate, calcium phosphate, zinc phosphate, manganese phosphate, and cadmium phosphate, and silicates such as sodium silicate, but thermosetting polyimide or epoxy resins are particularly preferred. These resin materials are easily cured by heating and have excellent heat resistance. This makes it possible to increase the ease of production and heat resistance of the powder magnetic core 11.

[0077] The ratio of the binder to the soft magnetic powder 1 varies slightly depending on the desired magnetic properties, mechanical properties, allowable eddy current loss, etc. of the powder core 11 to be produced, but is preferably about 0.3% by mass to 5.0% by mass, more preferably about 0.5% by mass to 3.0% by mass, and even more preferably about 0.7% by mass to 2.0% by mass. This makes it possible to obtain a coil component 10 with excellent magnetic properties while sufficiently binding the particles of the soft magnetic powder 1 together. If necessary, various additives may be added to the mixture for any purpose.

[0078] Examples of materials constituting the conductor 12 include highly conductive materials, such as metal materials including Cu, Al, Ag, Au, Ni, etc. Furthermore, an insulating film may be provided on the surface of the conductor 12 as necessary.

[0079] The shape of the powder magnetic core 11 is not limited to the ring shape shown in FIG. 2, but may be, for example, a ring shape in which part of the ring is missing, a shape in which the longitudinal direction is linear, or a sheet or film shape.

[0080] The dust core 11 may contain soft magnetic powder other than the soft magnetic powder 1 according to the embodiment described above or non-magnetic powder, as necessary.

[0081] 3.2.Closed magnetic circuit type Next, a closed magnetic circuit type coil component, which is an example of a magnetic element according to the embodiment, will be described.

[0082] FIG. 3 is a see-through perspective view that typically shows a closed magnetic circuit type coil component. The closed magnetic circuit type coil component 20 will be described below, but the following description will focus on the differences from the toroidal type coil component 10, and descriptions of similar points will be omitted.

[0083] As shown in FIG. 3, the coil component 20 according to this embodiment is formed by embedding a conductor wire 22 formed into a coil shape inside a powder magnetic core 21. That is, the coil component 20, which is a magnetic element, includes a powder magnetic core 21 containing the soft magnetic powder 1 described above, and is formed by molding the conductor wire 22 with the powder magnetic core 21. This powder magnetic core 21 has a similar configuration to the powder magnetic core 11 described above. This makes it possible to improve the magnetic characteristics of the powder magnetic core 21, as well as to increase the withstand voltage and reduce iron loss. Therefore, when the coil component 20 is mounted on an electronic device or the like, it is possible to improve the performance and reduce the size of the electronic device or the like.

[0084] Furthermore, because the conductive wire 22 is embedded inside the powder core 21, a gap is unlikely to occur between the conductive wire 22 and the powder core 21. This makes it possible to suppress vibrations caused by magnetostriction of the powder core 21, and also to suppress the generation of noise associated with this vibration.

[0085] The shape of the powder magnetic core 21 is not limited to the shape shown in FIG. 3, and may be a sheet, a film, or the like.

[0086] Furthermore, the dust core 21 may contain soft magnetic powders other than the soft magnetic powder 1 according to the embodiment described above and non-magnetic powders, as necessary.

[0087] 4.Electronic equipment Next, an electronic device including the magnetic element according to the embodiment will be described with reference to FIGS.

[0088] Fig. 4 is a perspective view showing a mobile personal computer, which is an electronic device including a magnetic element according to the embodiment. The personal computer 1100 shown in Fig. 4 includes a main body 1104 including a keyboard 1102, and a display unit 1106 including a display unit 100. The display unit 1106 is rotatably supported by the main body 1104 via a hinge structure. Such a personal computer 1100 includes a magnetic element 1000, such as a choke coil or inductor for a switching power supply, or a motor.

[0089] Fig. 5 is a plan view showing a smartphone, which is an electronic device including the magnetic element according to the embodiment. The smartphone 1200 shown in Fig. 5 includes a plurality of operation buttons 1202, an earpiece 1204, and a mouthpiece 1206. A display unit 100 is disposed between the operation buttons 1202 and the earpiece 1204. Such a smartphone 1200 includes a built-in magnetic element 1000, such as an inductor, a noise filter, or a motor.

[0090] 6 is a perspective view showing a digital still camera, which is an electronic device including the magnetic element according to the embodiment. The digital still camera 1300 photoelectrically converts an optical image of a subject using an imaging element such as a CCD (Charge Coupled Device) to generate an imaging signal.

[0091] 6 includes a display unit 100 provided on the back of a case 1302. The display unit 100 functions as a viewfinder that displays a subject as an electronic image. In addition, a light receiving unit 1304 including an optical lens, a CCD, etc. is provided on the front side of the case 1302, i.e., on the back side in the figure.

[0092] When the photographer checks the subject image displayed on the display unit 100 and presses the shutter button 1306, the image signal of the CCD at that time is transferred to and stored in memory 1308. Such a digital still camera 1300 also has a built-in magnetic element 1000, such as an inductor or a noise filter.

[0093] Examples of electronic devices according to the embodiments include the personal computer of FIG. 4, the smartphone of FIG. 5, and the digital still camera of FIG. 6, as well as mobile phones, tablet terminals, watches, inkjet discharge devices such as inkjet printers, laptop personal computers, televisions, video cameras, video tape recorders, car navigation devices, pagers, electronic organizers, electronic dictionaries, calculators, electronic game devices, word processors, workstations, videophones, security television monitors, electronic binoculars, POS terminals, medical devices such as electronic thermometers, blood pressure monitors, blood glucose meters, electrocardiogram measuring devices, ultrasonic diagnostic devices, and electronic endoscopes, fish finders, various measuring devices, instruments for vehicles, aircraft, and ships, mobile object control devices such as automobile control devices, aircraft control devices, railway vehicle control devices, and ship control devices, and flight simulators.

[0094] As described above, such electronic devices include the magnetic element according to the embodiment, which provides the effects of the magnetic element according to the embodiment, that is, the powder magnetic core having good magnetic properties, high voltage resistance, and low iron loss, and can improve the performance and reduce the size of the electronic devices.

[0095] 5. Advantages of the above embodiment As described above, the soft magnetic powder 1 according to the embodiment has metal particles 2 and oxide particles 3 present on the surfaces of the metal particles 2. The overall composition of the soft magnetic powder 1 is composed of Fe as a main component, Si with a content of 2.5% by mass or more and 7.5% by mass or less, Cr with a content of 1.0% by mass or more and 10.0% by mass or less, S with a content of 0.0020% by mass or more and 0.0070% by mass or less, and impurities. The average particle size of the oxide particles 3 is 0.2 μm or more and 2.0 μm or less.

[0096] According to this configuration, it is possible to manufacture a green compact having good magnetic properties, and it is possible to obtain a soft magnetic powder 1 having high insulation between particles.

[0097] In the soft magnetic powder 1 according to the embodiment, the number of oxide particles 3 present in one metal particle 2 is 20 or less.

[0098] According to this configuration, the oxide particles 3 are less likely to affect the packing of the powder compact while ensuring the insulating properties of the oxide particles 3. This makes it possible to obtain a soft magnetic powder 1 that can be used to produce a high-density powder compact.

[0099] Moreover, the soft magnetic powder 1 according to the embodiment has an average particle size of 1.0 μm or more and 20.0 μm or less.

[0100] According to this configuration, the soft magnetic powder 1 obtained has high packing properties during compaction and can suppress eddy current loss in the compact.

[0101] In addition, in the soft magnetic powder 1 according to the embodiment, the Si content is 3.0% by mass or more and 4.5% by mass or less, and the Cr content is 1.0% by mass or more and 5.0% by mass or less.

[0102] According to this configuration, it is possible to improve the oxidation resistance of the soft magnetic powder 1 while maintaining the magnetic properties. As a result, the occupancy rate of oxides during compaction is kept particularly low, and it is possible to obtain the soft magnetic powder 1 from which a compact with good magnetic properties can be produced.

[0103] In the soft magnetic powder 1 according to the embodiment, the oxide particles 3 contain silicon oxide. According to this configuration, the soft magnetic powder 1 having particularly excellent insulation between particles is obtained.

[0104] In addition, in the soft magnetic powder 1 according to the embodiment, the density of the green compact obtained by compacting at a pressure of 294 MPa is 5.40 g / cm 3 More than 6.00g / cm 3 The following is the result.

[0105] According to this configuration, it is possible to obtain the soft magnetic powder 1 from which a green compact having sufficiently high magnetic permeability can be manufactured while ensuring insulation between particles.

[0106] The dust core according to the embodiment includes the soft magnetic powder according to the embodiment. This allows the soft magnetic powder to have high packing properties and good magnetic properties, and also allows the dust core to have high voltage resistance and low iron loss.

[0107] Moreover, the magnetic element according to the embodiment includes the powder magnetic core according to the embodiment, thereby providing a magnetic element with high performance and small size.

[0108] Moreover, the electronic device according to the embodiment includes the magnetic element according to the embodiment, which makes it possible to improve the performance and reduce the size of the electronic device.

[0109] The soft magnetic powder, the powder core, the magnetic element, and the electronic device of the present invention have been described above based on preferred embodiments, but the present invention is not limited thereto. For example, the shapes of the powder core and the magnetic element are not limited to those shown in the drawings, and may be any shape. EXAMPLES

[0110] Next, specific examples of the present invention will be described. 6. Manufacturing of soft magnetic powder 6.1. Sample No. 1 First, soft magnetic powder was obtained by water atomization. The composition of the obtained soft magnetic powder is shown in Table 1. The manufacturing conditions of the soft magnetic powder by water atomization are shown in Table 1.

[0111] The average particle size, average circularity, average particle size of oxide particles, number of oxide particles, and oxygen content of the obtained soft magnetic powder were measured. The ratio of the average particle size of oxide particles to the average particle size of the soft magnetic powder (particle size ratio) was also calculated. The measurement results and calculation results are shown in Table 1.

[0112] Furthermore, as the manufacturing conditions for the soft magnetic powder, the difference between the pouring temperature and the melting point, and the outside diameter of the molten metal stream are shown in Table 1.

[0113] 6.2. Samples No. 2 to 24 A soft magnetic powder was obtained in the same manner as in Sample No. 1, except that the composition of the soft magnetic powder was changed as shown in Table 1 or Table 2.

[0114] In Tables 1 and 2, among the soft magnetic powders of each sample number, those that correspond to the present invention are designated as "Examples", and those that do not correspond to the present invention are designated as "Comparative Examples".

[0115] 7. Evaluation of soft magnetic powder 7.1. Density of green compact The density was measured for the green compacts produced using the soft magnetic powder of each sample No. The measured densities were then evaluated in accordance with the following evaluation criteria. The evaluation results are shown in Tables 1 and 2.

[0116] A: Density is 5.50g / cm 3 That's all. B: Density 5.40g / cm 3 More than 5.50g / cm 3 is less than C: Density 5.40g / cm 3 is less than

[0117] 7.2. Magnetic permeability of powder compacts The magnetic permeability of the green compacts produced using the soft magnetic powder of each sample No. was measured by the method described above. The measured magnetic permeability was evaluated according to the following evaluation criteria. The evaluation results are shown in Tables 1 and 2.

[0118] A: Permeability is 26 or more B: Permeability is 24 or more and less than 26 C: Permeability is less than 24

[0119] 7.3.Electrical Resistance of Powder Compacts For the green compacts produced using the soft magnetic powder of each sample number, the electrical resistance value was measured by the method described below.

[0120] First, a lower punch electrode was set at the lower end of a cylindrical cavity of a mold having an inner diameter of 8 mm. Next, 0.7 g of soft magnetic powder was filled into the cavity. Next, an upper punch electrode was set at the upper end of the cavity. Then, the mold, lower punch electrode, and upper punch electrode were set in a load application device. Next, a load of 20 kgf was applied using a digital force gauge in a direction in which the distance between the lower punch electrode and the upper punch electrode decreased. Then, the electrical resistance value of the green compact between the lower punch electrode and the upper punch electrode was measured while the load was applied.

[0121] The measured electrical resistance values ​​were then relatively evaluated in accordance with the following evaluation criteria. The evaluation results are shown in Tables 1 and 2.

[0122] A: The electrical resistance is particularly high (particularly higher than sample No. 1). B: High electrical resistance (higher than sample No. 1) C: Electrical resistance is slightly high (slightly higher than sample No. 1) D: The lowest electrical resistance (same as sample No. 1)

[0123] [Table 1]

[0124] [Table 2]

[0125] As shown in Tables 1 and 2, it was confirmed that the soft magnetic powders of the respective Examples were capable of producing green compacts having high density, high magnetic properties (magnetic permeability), and high voltage resistance. [Explanation of symbols]

[0126] 1...soft magnetic powder, 2...metal particles, 3...oxide particles, 5...soft magnetic particles, 10...coil component, 11...powder core, 12...conductor, 20...coil component, 21...powder core, 22...conductor, 100...display unit, 1000...magnetic element, 1100...personal computer, 1102...keyboard, 1104...main body, 1106...display unit, 1200...smartphone, 1202...operation button, 1204...earpiece, 1206...mouthpiece, 1300...digital still camera, 1302...case, 1304...light receiving unit, 1306...shutter button, 1308...memory

Claims

1. Metal particles; Oxide particles present on the surfaces of the metal particles; having The overall composition is: Fe as the main component, Si having a content of 2.5% by mass or more and 7.5% by mass or less; Cr having a content of 1.0% by mass or more and 10.0% by mass or less; S having a content of 0.0020% by mass or more and 0.0070% by mass or less; Impurities, It is composed of The soft magnetic powder is characterized in that the average particle size of the oxide particles is 0.2 μm or more and 2.0 μm or less.

2. 2. The soft magnetic powder according to claim 1, wherein the number of said oxide particles present in one said metal particle is 20 or less.

3. 3. The soft magnetic powder according to claim 1, wherein the average particle size of the soft magnetic powder is 1.0 μm or more and 20.0 μm or less.

4. The Si content is 3.0 mass% or more and 4.5 mass% or less, 3. The soft magnetic powder according to claim 1, wherein the Cr content is from 1.0% by mass to 5.0% by mass.

5. The soft magnetic powder according to claim 1 or 2, wherein the oxide particles contain silicon oxide.

6. The density of the green compact obtained by powder compaction at a pressure of 294 MPa is 5.40 g / cm 3 6.00g / cm or more 3 3. The soft magnetic powder according to claim 1, wherein:

7. A dust core comprising the soft magnetic powder according to claim 1 or 2.

8. A magnetic element comprising the powder magnetic core according to claim 7.

9. An electronic device comprising the magnetic element according to claim 8.

Citation Information

Patent Citations

  • Iron-based soft magnetic alloy powder

    JP2020111826A